Technological Innovation and Urban Processes - Stefano Aragona (European Regional Science Association (ERSA), 2006)
Technological innovation pushes transformatioin, rennovation and urban regenaration of areas and services. Special attention is given to the major urban centres, for the most related to nationale and/or Ue policy (Ce, 2003; Ce, 2004). A number of important questions are emerging between the reinforcement of the bigger areas, both metropolitan and urban, and the smaller centres. Moreover, according with different institutional actors it would be better more balanced process of anthropization because environmental and social reasons (APAT, 2004). In Calabria there are very few towns with more then 15.000 residents, often they are isolated and in the internal land. It requires to connect these areas by network, to push the diffusion of innovation and technology, to build up the "educated technology" (Del Nord, 1991). As said in other place (Aragona, 2003), the region is becoming to partecipate to the global village and the Ue (Ue, 1994; 1995; 1996) have policies and areas of implementation (Information Society, POR Calabbria 2000-20006; RIS+ 2001-2002). The paper faces a number of questions continuing such a topic. How are changing some of these areas that have implemented the technological innovation? Which impact are making the strategies and the choices on the spatial, functional and social context. The social effectiveness related to the quality life, said by Gasparini (1990) does it better? Could it be the outcome due to the absence of concentrated localization as is the case of other territorial areas marked by the "reticular" network (Dematteis, 1990)? Above all it requires to evaluate, said that the technological facilities are present enough, the role plays by the innovation as engine for both the cultural and awareness growth. Push for and knowledge that overcomes the mere informatization and suggestes the e-government: a formation and information path dedicated to build up new tools for local action and planning in the global competition. Identification of new settlements and spatial criteria (Appold et al., 1990), construction of urban spaces as signs of the past (Augè, 2004) but also signals of a new development and of social choesion, new citizenship (Cacciari, 1991).
Keywords: 330